VALUE RELATED TO HUMANS AS SOCIAL CREATURES IN THE MYTH OF THE GOD OF KILISUCI: VALUE RELATED TO HUMANS AS SOCIAL CREATURES IN THE MYTH OF THE GOD OF KILISUCI - Raharjo, Resdianto (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2021)
Myth is part of the oral literature genre that must be explored, preserved, and developed, because it contains values ​​and functions that are useful for the lives of Indonesian people, especially rural communities. Myths can be used as a medium for ethical and moral education for the Indonesian people. This study uses a qualitative approach. The object of this research is the myth of Dewi Kilisuci. The data of this research is the value of humans as social beings in the myth of Dewi Kilisuci. The location of this research is Mount Kelud, on the border between Kediri and Blitar. The data collection method in this study used the techniques of (a) observation, (b) interviews, (c) recording, (d) recording, (e) documentation. The data analysis technique used an objective hermeneutic technique. Values ​​related to humans as social beings include the value of justice, the value of democracy, and the value of mutual assistance. The myth of Mount Kelud functions as (1) an entertainment tool, (2) a reinforcement of social institutions and cultural institutions, (3) a means of social criticism, (4) an educational tool, (5) developing the economy, and (6) forcing people to comply with the norms of the community. norms that still apply in society.